Atopic dermatitis in the elderly - Irawan, Yudo; Rihatmadja, Rahadi; Legiawati, Lili; Yusharyahya, Shannaz Nadia; Sularsito, Sri Adi (UI Scholars Hub, 2016)
Atopic dermatitis (AD) is a recurrent skin inflammation accompanied by itching. The incidence of AD is increasing worldwide. AD, which persists until elderly or with an onset during elderly, is known as senile AD. It has different prevalence and clinical features from other AD stages. Senile atopic dermatitis affects males more than females, which is different from other stages of AD. Skin manifestation of senile AD is similar with the adult stage of Hanifin-Rajka criteria, but can be atypical. The typical feature of senile AD is eczematous dermatitis around a free-lesion fossa. Other common clinical manifestations are erythroderma and non- specific chronic dermatitis. In the management of senile AD, changes related to aging process should be considered. Management of senile AD is complex, involves combined pharmacological treatment consists of topical and systemic agents, and non pharmacological aspects. Appropriate treatment considering effectiveness and safety will improve the quality of life of patients with senile AD.